RESEARCH ON THERMAL AGING OF INDUSTRIAL ROBOT CABLE SHEATH - ZHOU ChunLin; WU Can; YANG Kai; NI Jing (Jixie qiangdu)
In the long-term work of industrial robot cables,the mechanical properties will be insufficient due to aging,which will affect the normal operation of the robot. In this paper,the thermal aging test was carried out to accelerate the aging of CPE rubber at the same temperature,and the tensile test was carried out to select the tensile strength at break and the elongation at break. The mechanical properties of CPE rubber after aging were studied. The results show that with the increase in aging time,the tensile strength and elongation of CPE break with the aging time,showing a trend of decreasing first and then rising. And the tendency towards the elongation at break is a delay from the tensile strength of the fracture. The slope of the elastic phase of the CPE tensile curve is greatly affected by the aging time,while the strengthening phase is less affected by it. And the slope of the elastic stage decreases rapidly in the early stage of heating,and it picks up later. This can provide some basis for further research to improve cable performance and prolong its service life.